2014
DOI: 10.1159/000358642
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MicroRNA-29 and Collagen in Cardiac Muscle after Swimming Training in Myocardial-Infarcted Rats

Abstract: Background: Myocardial infarction (MI) is accompanied by cardiac growth, increased collagen deposition, cell death and new vascularization of the cardiac tissue, which results in reduced ventricular compliance. The MiRNA-29 family (29a, 29b, and 29c) targets mRNAs that encode collagens and other proteins involved in fibrosis. In this study we assessed the effects of swimming training (ST) on expression of the cardiac miRNA-29 family and on genes encoding collagen after MI in rats. Methods: ST consisted of 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 35 publications
4
52
0
2
Order By: Relevance
“…On the other hand, low levels of miRNA-29 were previously associated with fibrosis in myocardial infarction (95d). Recently, Melo et al (65) showed that swimming training restored cardiac miRNA-29a and -29c levels and prevented collagen type I and III expression on the border and in the remote regions of the myocardial infarction, suggesting the cardiac effect of exercise training in myocardial-infarcted rats as a way to prevent or minimize the harmful effects in CVD.…”
Section: Mirnas Cardiac Hypertrophy and Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, low levels of miRNA-29 were previously associated with fibrosis in myocardial infarction (95d). Recently, Melo et al (65) showed that swimming training restored cardiac miRNA-29a and -29c levels and prevented collagen type I and III expression on the border and in the remote regions of the myocardial infarction, suggesting the cardiac effect of exercise training in myocardial-infarcted rats as a way to prevent or minimize the harmful effects in CVD.…”
Section: Mirnas Cardiac Hypertrophy and Exercise Trainingmentioning
confidence: 99%
“…In contrast, exercise training-induced physiological cardiac hypertrophy presents cardioprotective effects and is not related to heart failure (74). Exercise training has been described as being able to counteract structural and functional cardiac changes in CVD by contributing to the phenotypical changes of pathological into physiological cardiac hypertrophy (31,65,73,74).…”
mentioning
confidence: 99%
“…In stable chronic heart failure, clinical studies have shown that long-term moderate physical training attenuates abnormal cardiac remodeling and improves functional capacity and quality of life [10,11,12,13]. In different cardiac injury models, exercise has been shown to attenuate left ventricular dilation, myocyte hypertrophy, myocardial fibrosis, mitochondrial dysfunction, myocyte calcium handling changes, sympathoexcitation, cardiac dysfunction, and improve inflammatory profile [14,15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…We also found that miR-29c was increased in two distinct exercise models . Consistently, Souza and Melo and colleagues found that the decrease in miR-29 (a and c) seen in failing rat hearts was attenuated by aerobic exercise training, resulting in decreased collagen expression (Melo et al 2014;Souza et al 2015) and suggesting that exercise-induced miR-29 could help mitigate fibrosis and thereby improve ventricular function. We found that overexpression of miR-222, which is also upregulated in two distinct exercise models, inhibited cardiac fibrosis by three-to fourfold after IRI .…”
Section: Cardiac Fibrosismentioning
confidence: 68%
“…Of note, miR-222 was upregulated in both HF groups (Souza et al 2015). Other miRNAs, including miR-1, -29, -126, and -214, have also been reported to change in both healthy and diseased hearts after exercise (da Silva et al 2012;Melo et al 2014Melo et al , 2015aZhao 2015). Given limited access to tissue, there are no clinical studies to date examining human cardiac miRNA alterations after exercise.…”
Section: Micrornas In Cardiovascular Exercise Responsementioning
confidence: 90%